Lawyering from the inside out : learning professional development through mindfulness and emotional intelligence / Nathalie Martin, University of New Mexico School of Law , with Joshua Alt, Kendall Kerew, Jennifer Laws ; illustrations by Pamela "Zen" Miller. - Martin, Nathalie, 1961-; Alt, Joshua; Kerew, Kendall; Laws, Jennifer L. (Cambridge University Press, 2018)
Law is a varied, powerful, and highly rewarding profession. Studies show, however, that lawyers have higher rates of alcoholism, divorce, and even suicide than the general population. Stress creates these poor outcomes, including the stress of dealing with other people's problems all day, the stress of spending excessive amounts of time at work, and the stress of being disconnected to what is most meaningful in life. Through mindfulness and emotional intelligence training, lawyers can improve focus, get more work done in less time, improve their interpersonal skills, and seek and find work that will make their lives more meaningful. This book is designed to help law students and lawyers of all experience levels find a sustainable and meaningful life in the field of law. This book includes journaling and other interactive exercises that can help lawyers find peace, focus, meaning, and happiness over a lifetime of practicing law.